EKSTRAKSI GLUKOMANNAN DARI TANAMAN ILES-ILES (Amorphophallus oncophillus) DENGAN PELARUT AIR DAN PENJERNIH KARBON AKTIF - Irene Nindita P; Noor Amalia; H Hargono (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Iles-iles (Amorphophallus oncophyllus) is a type of plant that is very potential to be developed  in terms of medical, industrial and food. ). Iles-iles contains high glucomannan, namely 45-65% (Arifin, 2001).. The purpose of this study is to determine the variables influencing the extraction process iles-iles becomes glucomannan, obtain optimum conditions and to search the influence of activated carbon. In this research there are two steps experiment, which is extraction and  analyzed glucomannan content. This research uses two levels design factorial method with three variables. Fixed variables used 35 grams of iles-iles flour. Free variables used solvent with low level (-) 400 ml and upper level (+) 800 ml, temperature with low level (-) 35°C and upper level (+) 50°C, and the weight of activated carbon with low level (-) 1,25 gr and upper level (+) 1,8 gr. In the experimental results can be seen that the most influental variable is the solvent. The less the amount of solvent, the more content glucomannan obtained. The result of glucomannan extraction after given the addition of activated carbon obtained colors more clearly. Iles-Iles optimum processing conditions to be glucomannan is the 300 ml solvent with the temperature is 35OC and the weight of activated carbon is 1,25 gram.